STUDI TENTANG BENTUK MOTIF HIAS ARAH HADAP DAN MAKNA MENHIR DI KENAGARIAN MAEK KABUPATEN LIMA PULUH KOTA PROVINSI SUMATERA BARAT - INDRA GUNAWAN, Dr. Syafwandi, M.Si., Drs. Erwin A, M.Sn. (Serupa The Journal of Art Education, 2017)
This study aim to determine the forms menhir, knowing decorative motifs found on the walls of the menhirs, interpret the direction of menhir and to know the meaning of the menhir. Subjects in this research are menhirs in KenagarianMaek. While the method used is qualitative research with descriptive approach. Descriptive method is used to describe the study of phenomena that are on the subject of research produced in the form of words, pictures, not numbers. The datacollecting technique is observation, communication (interview), and documentation. All the data obtained through stages of verification and presentation of data reduction, data analysis, and then concluded. In order to check the validity of the data, the test triangulation is conducted. Based on the processing and analysis of data, the findings are obtained as follows: 1). Form of menhirs in Kenagarian Maek diverse, like forms of animals and the handle of the knife. 2) Motif contained in megalith heritage of menhir in Kenagarian Maek are motifs form kaluak paku, Pucuak Rabuang, kuciang Lalok and pilin duo. 3).Direction of the menhir leads to a plateau of Mount Sago.